Final Report : Developing Leaders of Change in the Teaching of Large University Chemistry Classes. - Bedgood, Danny R.; Bridgeman, Adam; Buntine, Mark; Gardiner, Michael; Lim, Kieran; Mocerino, Mauro; Morris, Gayle; Pyke, Simon; Southam, Daniel; Yates, Brian; Zadnik, Marjan (Australian Learning and Teaching Council, 2012)
Final report from a project that was about leading change in the teaching of chemistry and science in large university classes. ALIUS is a collaboration of six Australian universities funded by an ALTC Leadership for Excellence Grant (LE8-818). The aims of this project lay in three domains: (1) development of project members as Science Learning Leaders; (2) development of the skills of project members in practice-based learning and teaching innovation; and (3) creation of a virtual Learning Hub. Methods used to achieve these aims were: (a) leadership-professional development in leadership specifically targeted at fostering change in academic teaching practice; (b) Learning and Teaching Innovation - the U.S. NSF funded POGIL project was used as a model for teaching innovation; experienced POGIL instructors and facilitators were brought from the U.S. to run workshops and consultancies with ALIUS project members to build member skills in teaching innovation; (c) the learning hub (http://www.alius.edu.au/) will serve as a resource to share experiences in building teaching innovation, developed materials, resources about innovative teaching methods. ALIUS ran over 45 workshops and seminars impacting over 750 academics and Learning and Teaching staff at 35 Australian and International Universities.